Effects of Ayres sensory integration therapy versus conservative treatment in autism spectrum disorder - Inam, Ramma; Shah, Saleh; Ullah, Muhammad Sana; Tariq, Tahreem; Ashraf, Hira (Journal of the Pakistan Medical Association, 2026)
The study was conducted to evaluate the effects of Ayres sensory integration therapy versus conservative treatment in autism spectrum disorder. In a prospective randomised controlled trial, we assessed pre- and post-intervention scores of both the intervention group (A) that took ASI and the control group (B) that received conservative treatment—only behaviour therapy, speech therapy, and educational activities of children with Autism Spectrum Disorder (ASD) —using sensory profile from Jan 2024 to July 2024. Thirty diagnosed ASD cases, age range 2–8 years, were randomly enrolled in both groups (n=15/group) at the RICCER Institute of Faisalabad. The intervention group (A) was noted to be significantly better in mean change as compared with the control group (B). Independent and paired t-test results showed significant relationship between ASI intervention group (A) and sensory integration dysfunction, while non-significant relationship between sensory integration dysfunction and conservative group (B) treatment (p> 0.05). Ayres Sensory Integration, an Occupational Therapy Approach, was significantly effective in developing socialisation, self-care, and aim accomplishment in comparison to conservative treatment in ASD. Key Words: Ayres Sensory Integration, Autism Spectrum Disorder, Conservative treatment, Behaviour therapy, Sensory Integration Dysfunction.